2020
DOI: 10.12720/jcm.15.9.652-660
|View full text |Cite
|
Sign up to set email alerts
|

Recycling 4.0 - Digitalization as a Key for the Advanced Circular Economy

Abstract: Recycling will become more and more important in the future. To fulfill the requirements of a more efficient recycling process and thus enable an eco-friendly handling of resources, modern technologies can be used. One of these modern technology streams is called Industry 4.0. This paper presents an approach to how Industry 4.0 can be integrated into recycling processes, resulting in Recycling 4.0. Electric vehicles and their traction batteries are used as an example. To enable a more efficient disassembly and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 10 publications
0
22
0
Order By: Relevance
“…The study suggested using IoT and ICT to improve the effectiveness and efficiency of a waste management system. Kintscher et al (2020) presented an approach of integrating I4.0 and recycling processes resulting in Recycling 4.0. To explore the possibility of integration, electric vehicles and their traction batteries were used as an example.…”
Section: Ce and Business Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study suggested using IoT and ICT to improve the effectiveness and efficiency of a waste management system. Kintscher et al (2020) presented an approach of integrating I4.0 and recycling processes resulting in Recycling 4.0. To explore the possibility of integration, electric vehicles and their traction batteries were used as an example.…”
Section: Ce and Business Modelsmentioning
confidence: 99%
“…Kintscher et al (2020) presented an approach of integrating I4.0 and recycling processes resulting in recycling 4.0. To explore the possibility of integration, electric vehicles and their traction batteries were used as an example.…”
Section: Review On Ce and Sustainable Practices In Digitalization Sce...mentioning
confidence: 99%
“…As for the recycling process, IoT would provide benefits in terms of monitoring and tracking [103], enabling looping [71,95]. Two relevant aspects emerged as connected to the adoption of IoT: first, to make proper decisions, data should be collected with an HVSYS perspective [74]; second, as many data would be collected, BDA becomes fundamental to manage the complexity [102]. Lastly, the use of ROB would facilitate the recycling process, while also bringing benefits from a social sustainability perspective [103].…”
Section: Dts Enabling the Loop Areamentioning
confidence: 99%
“…The study highlights the contribution of digital technologies toward social and environmental sustainability. Similarly, Kintscher et al (2020) presented an approach to incorporate digital technologies and the recycling process for the eco‐friendly handling of resources. The study considered examples of electric vehicles and their traction batteries.…”
Section: Literature Reviewmentioning
confidence: 99%